2018
DOI: 10.1186/s13058-018-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in arginine and energy metabolism, structural and signalling lipids in metastatic breast cancer in mice detected in plasma by targeted metabolomics and lipidomics

Abstract: BackgroundThe early detection of metastasis based on biomarkers in plasma may improve cancer prognosis and guide treatment. The aim of this work was to characterize alterations in metabolites of the arginine pathway, energy metabolism, and structural and signalling lipids in plasma in the early and late stages of murine breast cancer metastasis.MethodsMice were orthotopically inoculated with 4T1 metastatic breast cancer cells, and plasma was analysed along the pulmonary metastasis progression using LC-MS/MS-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 59 publications
3
35
2
Order By: Relevance
“…It is conceivable that the role of lipid metabolism in metastasis involves not only energy production but also that of a building block supplier for membrane biogenesis. Metabolic pathways involving fatty acid can also generate signaling lipids (45,46). Our own results, using high-resolution oxygen, confirmed the implication of lipid metabolism in metastasis.…”
Section: Discussionsupporting
confidence: 79%
“…It is conceivable that the role of lipid metabolism in metastasis involves not only energy production but also that of a building block supplier for membrane biogenesis. Metabolic pathways involving fatty acid can also generate signaling lipids (45,46). Our own results, using high-resolution oxygen, confirmed the implication of lipid metabolism in metastasis.…”
Section: Discussionsupporting
confidence: 79%
“…The robust increase in WBC count of 4T1 tumour-bearing mice was also reported previously (Wang et al, 2015), and was linked to medullary and extramedullary haematopoiesis (Younos et al, 2011, 2012), with expansion of myeloid-derived suppressor cells (MDSCs) promoting metastases development (Younos et al, 2011; Cao et al, 2014; Kus et al, 2018). The increased leukocytosis underlines robust cancer-associated systemic inflammation as evidenced also by increased plasma concentration of pro-inflammatory cytokines, e.g.…”
Section: Discussionsupporting
confidence: 69%
“…But slight variations among numerous spectra per each group collected in this work and also negative results of water vapor test, we rather exclude a strong effect of some of these factors on our analysis. Moreover, the comparison of our spectroscopic results with the targeted lipidomic analysis performed on the same animal 4T1 cancer model suggests that a fast and reagent‐free FTIR‐based screening of a small plasma volume properly corresponds to structural remodeling of lipids.…”
Section: Discussionmentioning
confidence: 76%
“…Figure IIIB shows that integral intensities of band at 1031 and 1153 cm −1 increase remarkably in the last stage of the breast cancer progression. LC/MS/MS measurements performed on plasma of the investigated here murine model has showed that concentrations of glycolytic intermediates hexoses‐phosphates, fructose‐1,6‐bi‐phosphate, and pentose‐phosphates are elevated only at the late metastatic phase , what suggests that spectral changes shown for the 1031 and 1153 cm −1 bands might be associated with this group of sugars. In turn, a graph in Figure IIIC shows a gradual decrease of other saccharides (1012/1054 cm −1 ) which is not unambiguously assigned to a specific group of these biomolecules.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation